Thyroid nodule location and the risk of thyroid cancer: What do we know? - Jasim, Sina; Gharib, Hossein (Journal of Diabetes and Endocrine Practice, 2021)
Thyroid nodules are common in clinical practice and are routinely evaluated with neck ultrasound. Multiple guidelines rely on sonographic features to assist physicians when deciding if nodules require observation or fine-needle aspiration (FNA). Existing classification systems for risk stratification of thyroid nodules are different but equally accurate. The purpose of this article is to review the significance of thyroid nodule location as an important factor in assessing the risk of malignancy. Several topical issues are addressed. (1) Thyroid nodule location and risk of differentiated thyroid cancer, (2) Thyroid nodule location and risk of nodal metastasis, (3) Thyroid nodule location and surgical approach, (4) Thyroid nodule location and stratifications systems (5) Conclusions and future direction. In conclusion, it is advisable not to reply solely on ultrasound-derived risk levels when evaluating thyroid nodules to determine optimal management including nodule FNA, follow-up or no additional intervention. This is likely because other clinically important features might not be accounted for when using those risk stratification algorithms. There are now reasonable data to suggest thyroid nodule location may be an additional prognostic predictor. In the lack of clear radiologic guidance, clinical judgment remains the main driving factor.
Keywords: Differentiated thyroid cancer; fine-needle aspiration; neck ultrasound; risk stratification systems; thyroid nodule location; thyroid nodules